2020
DOI: 10.1590/1678-4162-11322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyme essential oil on rumen parameters, nutrient digestibility, and nitrogen balance in wethers fed high concentrate diets

Abstract: This trial aimed to evaluate the effects of thyme essential oils (EO) on rumen parameters, nutrient digestibility and nitrogen balance in wethers fed with high-concentrate diet. Twenty rumen-cannulated wethers were blocked according to body weight (BW= 64.0±2.1kg), and received one of the following treatments: 25mg of monensin/kg of dry matter (DM; MON) or doses of thyme EO (1.25, 2.50 or 3.75g/kg of DM). The diet was composed of 90% concentrate. Thyme EO was composed mainly by thymol (46.6% of DM) and p-cymen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…The identified compounds are consistent with previously published studies investigating the compositional concentration of thyme, rosemary, and basil EOs [ 46 , 47 , 48 , 49 ]. It can be seen that the major compound identified within the thyme EO-functionalized samples is thymol and p-cymen-7-ol.…”
Section: Resultssupporting
confidence: 91%
“…The identified compounds are consistent with previously published studies investigating the compositional concentration of thyme, rosemary, and basil EOs [ 46 , 47 , 48 , 49 ]. It can be seen that the major compound identified within the thyme EO-functionalized samples is thymol and p-cymen-7-ol.…”
Section: Resultssupporting
confidence: 91%
“…It was found that higher proportion of Zn (170 mg/kg) had improved the nutrient digestibility of rabbits compared to non-treated control group [35]. Simultaneously, in this study, the nanoparticles of zinc oxide (ZnO-NPs; 100 mg/kg BW), thyme oil (THO; 500 mg/kg BW), or their combination significantly increased the dry matter, crude protein, ether extract, and crude fiber digestibility compared to each respective control group that could be attributed to improvement of enzymes' activities induced by zinc [39][40][41][42] in addition to the improved digestibility induced by thyme [43] as stated in other species.…”
Section: Discussionmentioning
confidence: 55%
“…For the most part, supplemental EO has not appreciably affected measures of apparent total tract digestion in dairy cattle [ 31 , 54 ], steers [ 9 , 55 , 56 ] and in lambs [ 10 , 57 , 58 ]. In several studies [ 54 , 57 , 59 ], supplemental essential oils were found to alter ruminal fermentation without effect on total tract digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports [ 6 , 7 , 8 ] indicate that mixtures of essential oils may result in similar or even greater enhancements in growth performance than MON. These effects may not be attributable to changes in digestion, as the effects of supplemental essential oils on total tract digestion are not appreciable [ 9 , 10 ]. Comparisons of essential oils vs. VM in ruminants is limited.…”
Section: Introductionmentioning
confidence: 99%